The effects of boxing glove design on thumb position when making a fist for striking - Peveler, W. W.; Schoffstall, J.; Coots, J.; Kilian, J.; Glauser, J. (The Journal of Strength and Conditioning Research, 2024)
It has been suggested that boxing glove design alters thumb position increasing the risk of injury. The purpose of this study was to determine the effects of boxing glove design on thumb joint angles when making a fist. Ten experienced fighters participated in this study. A DEXA scan was used to produce an x-ray image of thumb position for all conditions (no gloves and 10-oz boxing gloves). Mean values for dependent measures were compared using a paired-sample T test and an alpha of 0.05. The carpometacarpal (CMC) joint angle was significantly different between no glove (14.1 ± 6.54°) and boxing glove (34.2 ± 7.60°) at p = 0.001. The metacarpophalangeal (MP) joint angle was significantly different between no glove (132.6 ± 12.74°) and boxing glove (149.40 ± 8.15°) at p = 0.001. The IP joint angle was not significantly different between no glove (135.50 ± 19.12°) and boxing glove (144.40 ± 17.39°) at p = 0.269. The perpendicular distance from the second metacarpal of the hand to the center of the MP joint was significantly different between no glove (0.48 ± 0.54 cm) and boxing glove (1.84 ± 0.29 cm) at p = 0.001. Use of a boxing glove resulted in abduction of the thumb away from the hand and increased CMC and MP joint angles that were significantly different in relation to making a fist without a glove. Information from this study may provide insight into the high rate of thumb injury and provide insight for future boxing glove design.